1995
DOI: 10.1128/jb.177.13.3824-3829.1995
|View full text |Cite
|
Sign up to set email alerts
|

Phage operon involved in sensitivity to the Lactococcus lactis abortive infection mechanism AbiD1

Abstract: Phage bIL66 is unable to grow on Lactococcus lactis cells harboring the abortive infection gene abiD1. Spontaneous phage mutants able to grow on AbiD1 cells were used to study phage-Abi interaction. A 1.33-kb DNA segment of a mutant phage allowed growth of AbiD1 s phages in AbiD1 cells when present in trans. Sequence analysis of this segment revealed an operon composed of four open reading frames, designated orf1 to orf4. The operon is transcribed 10 min after infection from a promoter presenting an extended ؊… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 31 publications
0
93
0
Order By: Relevance
“…Recently, a sequence (TtTGt-TATAAT) with no -35 site was identified by primer ex- Liu,HARVEY,and DUNK Vol. 43 tension within the phage bIL66 DNA in L. lactis (Bidnenko et al, 1995). To our knowledge, this study represents the first instance in L. lactis demonstrating the requirement of an extended motif for its promoter function in the absence of a -35 site.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, a sequence (TtTGt-TATAAT) with no -35 site was identified by primer ex- Liu,HARVEY,and DUNK Vol. 43 tension within the phage bIL66 DNA in L. lactis (Bidnenko et al, 1995). To our knowledge, this study represents the first instance in L. lactis demonstrating the requirement of an extended motif for its promoter function in the absence of a -35 site.…”
Section: Discussionmentioning
confidence: 93%
“…Lactococcal phages used in this study (bIL170,bIL15,bIL77,bIL120,bIL191) are from our collection and belong to the 936 group as determined by DNA hybridization (B. Cesselin, unpublished results). They were propagated on appropriate Lactococcus lactis strains (IL1403 for bIL170) at 30 mC in M17 broth supplemented with 5 g glucose l − " and 10 mM CaCl # (Bidnenko et al, 1995). Escherichia coli XL1-Blue MRFh (Stratagene), transformed with pBluescript derivatives, was cultivated in Luria-Bertani broth (Maniatis et al, 1982) with 100 µg ampicillin ml − ".…”
Section: Methodsmentioning
confidence: 99%
“…They belong to different structural families and could have diverse physiological roles in replication, recombination, repair, maturation or packaging of phage DNA. gp3 of bIL66 is homologous to the E. coli RuvC Holliday-junction resolvase (Bidnenko et al, 1998) and has been shown to be involved in phage Sequence analysis of lactococcal phage bIL170 sensitivity to the AbiD1 abortive infection mechanism (Bidnenko et al, 1995). Its exact role in phage development is still unknown, but it is most probably essential for phage multiplication under certain conditions (Bidnenko et al, 1995).…”
Section: Dna Endonucleasesmentioning
confidence: 99%
“…The plasmid was subcloned by ligation of a partial Sau3A digest with a BamHI digest of pBluescript SK + . The ligation mixture was used to transform E. coli XL-1 Blue and Lytic phage for IL1403 Bidnenko et al (1995) transformants were selected on plates containing X-Gal. Plasmid DNA from individual white colonies was isolated, checked for the presence of inserts and used for sequence analysis that was performed with an Applied Biosystems 373A automated DNA sequencer.…”
Section: Methodsmentioning
confidence: 99%